2012
DOI: 10.2174/157015912804143577
|View full text |Cite
|
Sign up to set email alerts
|

Redox Signaling Pathways Involved in Neuronal Ischemic Preconditioning

Abstract: There is extensive evidence that the restoration of blood flow following cerebral ischemia contributes greatly to the pathophysiology of ischemia mediated brain injury. The initiating stimulus of reperfusion injury is believed to be the excessive production of reactive oxygen (ROS) and nitrogen (RNS) species by the mitochondria. ROS and RNS generation leads to mitochondrial protein, lipid and DNA oxidation which impedes normal mitochondrial physiology and initiates cellular death pathways. However not all ROS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 182 publications
(125 reference statements)
1
33
0
Order By: Relevance
“…Hormesis elicits U-shaped or biphasic responses to stress and is mediated, at least in part, by the co-ordinated network of vitagenes (8)(9)(10)20). Preconditioning increases the expression of the vitagenes thioredoxin, sirtuin-1, Hsp32, and Hsp70 (1,2,16,59). In the present study, we also found that Hsp32 and Hsp70 were increased by PI preconditioning.…”
Section: Ape1 Preserves Neuronal Structure and Functionsupporting
confidence: 72%
“…Hormesis elicits U-shaped or biphasic responses to stress and is mediated, at least in part, by the co-ordinated network of vitagenes (8)(9)(10)20). Preconditioning increases the expression of the vitagenes thioredoxin, sirtuin-1, Hsp32, and Hsp70 (1,2,16,59). In the present study, we also found that Hsp32 and Hsp70 were increased by PI preconditioning.…”
Section: Ape1 Preserves Neuronal Structure and Functionsupporting
confidence: 72%
“…However, not all ROS production is detrimental. Low levels of ROS are protective and may serve as a trigger for activation of numerous pathways (PKCe, SIRT1, Nrf-2, and HIF-1) [57,58]. These pathways increase the activation of antioxidant enzymes (glutathione synthase, heme oxygenase, catalase, glutathione, and manganese superoxide dismutase), expression of angiogenic (erythropoetin), and survival proteins (MAPK) [57].…”
Section: Cellular Defense Effectsmentioning
confidence: 99%
“…Low levels of ROS are protective and may serve as a trigger for activation of numerous pathways (PKCe, SIRT1, Nrf-2, and HIF-1) [57,58]. These pathways increase the activation of antioxidant enzymes (glutathione synthase, heme oxygenase, catalase, glutathione, and manganese superoxide dismutase), expression of angiogenic (erythropoetin), and survival proteins (MAPK) [57]. Hypothermic machine perfusion may also exert upregulation of defense pathways through minor ROS release during cold perfusion, especially in livers exposed to warm ischemia before perfusion (DCD grafts) (Fig.…”
Section: Cellular Defense Effectsmentioning
confidence: 99%
“…Ischemic preconditioning also has translational potential; remote ischemic preconditioning of an arm or leg with a tightened blood pressure cuff may protect distant organs from ischemic events such as stroke and cardiac bypass surgery (Fairbanks and Brambrink 2010;Candilio et al 2011). The state of our knowledge on ischemic preconditioning has been discussed in many recent reviews (Dirnagl and Meisel 2008;Della-Morte et al 2012;Kitagawa 2012;Prabhakar and Semenza 2012;Thompson et al 2012) and will not be described further here.…”
Section: Adaptation and Sensitization To Proteotoxic Stressmentioning
confidence: 99%
“…The word 'hit' is not typically used in reference to sublethal stress even though it elicits transient damage (for an example, see Dembinski et al 2006). Sublethal preconditioning stimuli also increase reactive oxygen species and activate the caspase cascade (McLaughlin et al 2003;Thompson et al 2012). Without sublethal injury, there would be no stress response because the sensors would not recognize any perturbations.…”
Section: Adaptation and Sensitization To Proteotoxic Stressmentioning
confidence: 99%